Studies on the inhibitory effect of isavuconazole on flumatinib metabolism in vitro and in vivo - Liu, Ya-nan; Xu, Xinhao; Nie, Jingjing; Hu, Yingying; Xu, Xuegu; Xu, Ren-ai; Du, Xiaoxiang (Frontiers in Pharmacology, 2023)
As the validated agent for the treatment of chronic myelogenous leukemia (CML), flumatinib is a novel oral tyrosine kinase inhibitor (TKI) with higher potency and selectivity for BCR-ABL1 kinase compared to imatinib. Many patients experience aspergillosis infection and they may start using isavuconazole, which is an inhibitor of CYP3A4. However, there is no study on their interaction in vitro and in vivo. In the present study, the concentrations of flumatinib and its major metabolite M1 were rapidly determined using an stable ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method. The half-maximal inhibitory concentration (IC50) was 6.66 μM in human liver microsomes (HLM), while 0.62 μM in rat liver microsomes (RLM) and 2.90 μM in recombinant human CYP3A4 (rCYP3A4). Furthermore, the mechanisms of inhibition of flumatinib in HLM, RLM and rCYP3A4 by isavuconazole were mixed. In pharmacokinetic experiments of rats, it was observed that isavuconazole could greatly change the pharmacokinetic parameters of flumatinib, including AUC(0-t), AUC(0-∞), Cmax and CLz/F, but had no effect on the metabolism of M1. According to the results of in vitro and in vivo studies, the metabolism of flumatinib was inhibited by isavuconazole, suggesting that isavuconazole may raise the plasma concentration of flumatinib. Thus, it is important to take special care of the interactions between flumatinib and isavuconazole in clinical applications.